2016
DOI: 10.1128/msphere.00036-15
|View full text |Cite
|
Sign up to set email alerts
|

PprA Protein Is Involved in Chromosome Segregation via Its Physical and Functional Interaction with DNA Gyrase in Irradiated Deinococcus radiodurans Bacteria

Abstract: D. radiodurans is one of the most radiation-resistant organisms known. This bacterium is able to cope with high levels of DNA lesions generated by exposure to extreme doses of ionizing radiation and to reconstruct a functional genome from hundreds of radiation-induced chromosomal fragments. Here, we identified partners of PprA, a radiation-induced Deinococcus-specific protein, previously shown to be required for radioresistance. Our study leads to three main findings: (i) PprA interacts with DNA gyrase after i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 68 publications
(104 reference statements)
0
19
0
Order By: Relevance
“…In particular the pprA mutant of D. radiodurans was shown to be very sensitive to gamma radiation, and therefore the absence of pprA in D. proteolyticus is intriguing. PprA binds to DNA, interacts with gyrase, and is required for accurate chromosome segregation after exposure of D. radiodurans to ionizing radiation (Devigne et al, 2016;Kota, Charaka, Ringgaard, Waldor, & Misra, 2014;Narumi et al, 2004). DdrA binds to single-stranded DNA and is proposed to be part of a DNA end-protection system that helps to preserve genome integrity after exposure to ionizing radiation (Harris et al, 2004).…”
Section: Radiation-tolerantmentioning
confidence: 99%
“…In particular the pprA mutant of D. radiodurans was shown to be very sensitive to gamma radiation, and therefore the absence of pprA in D. proteolyticus is intriguing. PprA binds to DNA, interacts with gyrase, and is required for accurate chromosome segregation after exposure of D. radiodurans to ionizing radiation (Devigne et al, 2016;Kota, Charaka, Ringgaard, Waldor, & Misra, 2014;Narumi et al, 2004). DdrA binds to single-stranded DNA and is proposed to be part of a DNA end-protection system that helps to preserve genome integrity after exposure to ionizing radiation (Harris et al, 2004).…”
Section: Radiation-tolerantmentioning
confidence: 99%
“…Interestingly, possible functions of pleiotropic PprA have been investigated by observing a deficient strain during cell division after radiation exposure (28). PprA could directly interact with gyrase subunit A but not subunit B in the heterotetramer, stimulating DNA relaxation and initial supercoiling while inhibiting complete formation of the supercoiled plasmid for gyrase (30,31). Furthermore, the dimer mutant of W183R does not bind to any subunits of gyrase (30), suggesting that the interaction region for gyrase is located near Interface 2 with C2 symmetry.…”
Section: Discussionmentioning
confidence: 99%
“…PprA can directly interact with the genome-partitioning proteins ParA1 and ParA4 and with DNA gyrase in vivo (29,30). DNA decatenation and supercoiling activities are stimulated by PprA protein (30,31). Furthermore, transgenic E. coli expressing PprA exhibits higher resistance to oxidative stress by increasing catalase activity (32).…”
mentioning
confidence: 99%
“…Recently, the role of PprA in genome maintenance and cell division has been reported (Devigne et al, 2013;Kota et al, 2014a). It has also been demonstrated that PprA interacts with deinococcal DNA topoisomerase in vivo and modulates its functions in vitro (Kota et al, 2014b(Kota et al, , 2016Devigne et al, 2016). …”
Section: Radiodurans R1 Amentioning
confidence: 99%